"Tryin' to Survive": Black Male Students' Understandings of the Role of Race and Racism in the School-to-Prison Pipeline. Issue 4 (2nd October 2019) - Grace, Jennifer E.; Nelson, Steven L.
ABSTRACT: This article examines Black male students' perceptions of the role of race and racism in perpetuating the school-to-prison pipeline. Through a phenomenological investigation of ten Black male students in the New Orleans area, this article finds that Black male students perceive racism in society, racism in schools, and poor teacher expectations to aid in the perpetuation of the school-to-prison pipeline. Furthermore, the participants of this study revealed that schools may use other Black males who have successfully navigated the educational system to better reach Black male students who are placed at risk of the school-to-prison pipeline. This article considers the responses of theses Black male students to the role of race and racism in the context of critical race theory.